Compulsory Vaccination for Children in Malaysia: Legislation and Realisation - Nurul Jannah binti Mustafa Khan; Zuhaira Nadiah binti Zulkipli (Universitas Airlangga, 2018)
For ages, it has been proven that vaccines are among the most effective tools in preventing infectious diseases from spreading in the population of human beings. The result of high immunization coverage is the drastic deteriorations in vaccinepreventable diseases. Hence, it is indeed disturbing to see the report by Ministry of Health that the number of cases of parents refusing vaccination for their children is escalating, for an example, measles and pertussis cases to rise. Whether these parents realized it or not, they had denied the right of their children to be vaccinated against preventable diseases that had been in control all this while because of vaccines, and more, jeopardizing the public health as well. For this reason, the Ministry of Health has contemplated making vaccination compulsory for children as to protect them against preventable diseases and for the benefit of the society as a whole. This article discusses the extent of the regulations that may be implemented. Therefore for the purpose of this article, the scrutinization of vaccination law as implemented in California will be referred. At the end of this article, some recommendations are proposed in relation to the realization of legislation of vaccination regulations that may be implemented by the government, hopefully soon. This article employs a doctrinal analysis and secondary data from academic journals and online databases.